A genetic strategy for stochastic gene activation with regulated sparseness (STARS). - Sheng-Zhi Wang; Bao-Hua Liu; Huizhong W Tao; Kun Xia; Li I Zhang (PLoS ONE)
It remains a challenge to establish a straightforward genetic approach for controlling the probability of gene activation or knockout at a desired level. Here, we developed a method termed STARS: stochastic gene activation with genetically regulated sparseness. The stochastic expression was achieved by two cross-linked, mutually-exclusive Cre-mediated recombinations. The stochastic level was further controlled by regulating Cre/lox reaction kinetics through varying the intrachromosomal distance between the lox sites mediating one of the recombinations. In mammalian cell lines stably transfected with a single copy of different STARS transgenes, the activation/knockout of reporter genes was specifically controlled to occur in from 5% to 50% of the cell population. STARS can potentially provide a convenient way for genetic labeling as well as gene expression/knockout in a population of cells with a desired sparseness level.